2021
DOI: 10.3390/vaccines9121487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pope Francis’ Religious Authority and Media Coverage on Twitter User’s Attitudes toward COVID-19 Vaccination

Abstract: This paper is interdisciplinary and combines the research perspective of medical studies with that of media and social communication studies and theological studies. The main goal of this article is to determine [from arguments on all sides of the issue] whether, and to what extent, statements issued by a religious authority can be used as an argument in the COVID-19 vaccination campaign. The authors also want to find answers to the questions of how the pope’s comments affect public opinion when they concern t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In addition, Catholic leaders in the US and Canada have raised concerns about some COVID-19 vaccines made using aborted fetal cells [ 53 ]. Of course, other moral and theological arguments could be made to support vaccination—for example, Pope Francis indicated that vaccination was a moral obligation [ 54 ]. The clergy may hold complex views on vaccination [ 55 ] but could nonetheless be important sources of information and education about vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Catholic leaders in the US and Canada have raised concerns about some COVID-19 vaccines made using aborted fetal cells [ 53 ]. Of course, other moral and theological arguments could be made to support vaccination—for example, Pope Francis indicated that vaccination was a moral obligation [ 54 ]. The clergy may hold complex views on vaccination [ 55 ] but could nonetheless be important sources of information and education about vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…85 Gawel and co-workers explored did Pope Francis words have an effect on Catholics' decisions to accept or refuse the COVID-19 vaccination, and although it is estimated that it did reach the public its' effectiveness is quite questionable. 86 The degree of polarization of views / content regarding COVID-19 vaccination on social networks There were 28 studies that examined the degree of polarization of social media content related to COVID-19 vaccines (Table 3). The degree of polarization mainly reflected the rate of positive versus negative views on specific COVID-19 vaccine-related content, expressed as either likes vs. dislikes or supporting vs. disapproving content.…”
Section: Countries December 2020 -March 2021mentioning
confidence: 99%
“…Recently, the effects of Pope Francis’ religious authority have been investigated by analyzing Twitter users’ attitudes toward COVID-19 vaccination after the Pope addressed the matter by inviting everyone to get an anti-COVID-19 shot in order to stem the virus diffusion ( 41 ). It resulted that, while the Pope’s appeal would not convince those with firm beliefs against vaccinations, the ones in favor of vaccination would be provided with additional arguments in the debate and those who are undecided and looking for information to decide on the area of their faith could be encouraged by their leader’s voice on the topic ( 43 ). It would be interesting to perform further investigations on the topic, assessing whether following religious norms can have as counterpart a spontaneous adherence to social and institutionalized norms too, as opposed to a significant refuse of blind acceptance of rules by non-believers, who hold a more skeptical vision and henceforth tend to explore their options from different sources before complying with a law.…”
Section: Discussionmentioning
confidence: 99%